Bully breath how to tame a troublemaker (New Jersey : Meridian Education Corporation, 1997)
This video encourages students to talk about the often'under wraps' topic. The program offers bullies good reason to stop treating stress badly. it provides techniques that victims can use to stop bully in his or her tracks.
Keywords: Bullying